2022
DOI: 10.3390/en16010293
|View full text |Cite
|
Sign up to set email alerts
|

Current Electromagnetic Compatibility Problems of High-Power Industrial Electric Drives with Active Front-End Rectifiers Connected to a 6–35 kV Power Grid: A Comprehensive Overview

Abstract: Today, electric drive systems based on frequency converters with active front-end rectifiers (FC-AFEs) are widespread across industries. In the course of the upgrade of production facilities, such systems replace the conventional converters with thyristor- and diode-based rectifiers. FC-AFEs have the following advantages: the capacity to regenerate the power to the grid and the capacity to operate at the set power factor. The manufacturers of FC-AFEs also claim that their products have the best electromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This emphasizes greater errors over MAE. RMSE is the square root of MSE, which provides a more interpretable measure of error, being displayed in Equation (14).…”
Section: 2 Root Mean Square Errormentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes greater errors over MAE. RMSE is the square root of MSE, which provides a more interpretable measure of error, being displayed in Equation (14).…”
Section: 2 Root Mean Square Errormentioning
confidence: 99%
“…These high power consumers use a lot of electricity and can have an impact on power quality via reactive power, low power factor, and electric current harmonics [6][7][8]. The largest consumers of electric power in steel plants are EAF [5,9,10], but rolling mills also have significant power and produce harmonic currents [11,12], overcurrents that cause reactive power and low power factor [13,14] or flicker [12].…”
Section: Introductionmentioning
confidence: 99%
“…At different m values, the converted power quality parameters change. The relevant studies in the area have shown that the higher the m value, the lower the THD of the converter output voltage [19][20][21][22][23]. In practice, the m value close to 1 (if we describe a range from 0 to 4/π) is chosen while providing a margin for maintaining stable AFE and VSI operation in dynamic modes (a voltage drop in the DC link during shock application of the electric drive load) [24][25][26][27].…”
Section: Eafe Egmentioning
confidence: 99%
“…Some studies [29,30] consider searching for SHE PPWMs to bypass the resonance region of the grid impedance frequency response to improve the voltage quality at the connection point of industrial consumers to a common grid. However, the papers describe only experimental methods to estimate the impact of converters without preliminary calculation of the spectra of current induced by supply voltage distortions under the conditions of existing power grid modes.…”
Section: Overview Of Studies and Problem Statementmentioning
confidence: 99%